Pemberdayaan Masyarakat Melalui Gerakan Sayang Perempuan Ojek Online (GASPOL) di Kota Surabaya - Devi Alvionita; Eldaffa Zulano Alya; Alviyah Iriani; Zaskia Naurah Salsabila Al Syahfitri Syahfitri; Aril Maulana; Tauran Ardiyansah (Jurnal Wanita dan Keluarga, 2026)
Female online motorcycle taxi drivers in Surabaya often face dual vulnerabilities, including economic uncertainty, domestic burdens, and threats of sexual violence in public spaces. This study aims to analyze the empowerment process of these female drivers through the Gerakan Sayang Perempuan Ojek Online (GASPOL) program. Utilizing a descriptive qualitative approach, data were collected through in-depth interviews, observation, and documentation, analyzed through Najiati's four dimensions of empowerment: equality, participation, independence, and sustainability. The results indicate that the GASPOL program successfully creates an equal, safe space and encourages active participation through informal thematic coordination groups. In terms of independence, micro-business and makeup training have proven to strengthen domestic economic resilience, coupled with enhanced self-protection through legal and physical briefing. Meanwhile, sustainability is pursued through a rotating class system, cooperative formation plans, and access to people's business credit (KUR) and social security (BPJS Ketenagakerjaan). In conclusion, this program effectively stimulates the capacity of female drivers despite ongoing budget constraints. It is recommended that the DP3AK of East Java Province expand public education to eliminate gender stigma and immediately establish collaborative governance with online transportation application companies to ensure comprehensive protection within the working ecosystem.